Bravo Pueblo: interpretación del montaje escénico del colectivo coreográfico Indoamericanto para el Carnaval de Negros y Blancos 2022 - Olaya Mesías, Karen Sophia; Salcedo Nieto, Jeisson Andrés (Universidad Antonio Nariño, 2023)
This document it is an investigation regarding Indoamericanto choreographic group and their work “Bravo Pueblo” for the “Negros and Blancos carnival” in 2022, wherein they operate autonomously and decide to make a job of choreographic to the Pasto city this job it is our base to realize this investigation. This choreographic group were select for us base on it is extensive experience in the Negros y Blancos Carnival.